Plasma Lipid Metabolites are Associated with Gestational Age but Not Bronchopulmonary Dysplasia - Rogers, Lynette K. (2012)
AIM: To test the hypothesis that plasma lipid metabolite levels in premature infants are associated with the development of bronchopulmonary dysplasia (BPD). The studies also tested a secondary hypothesis that plasma lipid metabolite levels were correlated with gestational age. METHODS: Infants born less than 32 weeks gestation were enrolled during the first 72 hours of life. Plasma samples were obtained and lipid levels were measured by LC-MS/MS. Clinical data were collected to determine infant outcomes and BPD diagnosis. RESULTS: Following adjustment for confounders, lipid levels were not associated with BPD; however, levels of specific lipid metabolites were correlated with gestational age. CONCLUSION: Immature lipid metabolism pathways in premature infants may contribute to the pathogenesis of BPD and other diseases.